2021
DOI: 10.37616/2212-5043.1208
|View full text |Cite
|
Sign up to set email alerts
|

Right Atrial Volume Index as a Predictor of Persistent Right Ventricular Dysfunction in Patients with Acute Inferior Myocardial Infarction and Proximal Right Coronary Artery Occlusion Treated with Primary Percutaneous Coronary Intervention

Abstract: Objectives Patients with right ventricular (RV) infarctions associated with inferior infarctions have higher rates of adverse events than isolated inferior infarctions. Right atrial volume index (RAVI) has recently been described as a predictor of clinical outcome in patients with chronic systolic heart failure and pulmonary hypertension. The aim of this study is to assess the ability of RAVI to predict the persistent RV dysfunction after acute inferior STEMI due to occlusion of proximal RCA. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…erefore, patients treated with chemoradiotherapy often take drugs to protect organs and reduce the impact of chemoradiotherapy on other organ functions. Anthracyclines are commonly used chemotherapeutic drugs in clinic, which play a significant role in the treatment and control of various visible tumors and hematological tumors, with excellent treatment results [18][19][20]. However, clinical trials have shown that anthracyclines have a great impact on myocardial function of patients, and chemotherapy with anthracyclines may cause myocardial damage in patients.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, patients treated with chemoradiotherapy often take drugs to protect organs and reduce the impact of chemoradiotherapy on other organ functions. Anthracyclines are commonly used chemotherapeutic drugs in clinic, which play a significant role in the treatment and control of various visible tumors and hematological tumors, with excellent treatment results [18][19][20]. However, clinical trials have shown that anthracyclines have a great impact on myocardial function of patients, and chemotherapy with anthracyclines may cause myocardial damage in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional (2DE) and three-dimensional (3DE) echocardiography are the most commonly employed noninvasive imaging techniques to evaluate RA size [11] , [12] , [13] . Volumetric assessment of the RA size may be more accurate than linear measurement because RA enlargement is asymmetrical.…”
Section: Ra Sizementioning
confidence: 99%
“…The cutoff value of RAVI 30 mL/m 2 had a 87.5% sensitivity, a 92.24% specificity for predicting persistently impaired RV function. 9 The importance of predicting persistence RV dysfunction came from the fact that persistent RV dysfunction is associated with long term poor prognosis irrespective of LV systolic function. 10,11 Liao et al, outcomes between left ventricular myocardial infarction patients with and without RV myocardial infarction (RVMI) in 458 patients with acute (STEMI) undergoing primary percutaneous coronary intervention.…”
Section: Measurement Of Ra Volume Index (Ravi)mentioning
confidence: 99%